(2023 Volume 6) The Best Constant For An Inequality

Download as pdf or txt
Download as pdf or txt
You are on page 1of 5

The Best Constant for an Inequality from

Mathematical Reflections
Titu Andreescu, Marius Stănean

In Mathematical Reflections 1 (2018), Alessandro Ventullo proposed the following inequality:

S435. Let a, b, c be positive real numbers such that abc = 1. Prove that
8
a3 + b3 + c3 + ≥ 4.
(a + b)(b + c)(c + a)
Here is one possible solution:

Starting from the inequality

x3 + y 3 ≥ xy(x + y) ⇐⇒ (x + y)(x − y)2 ≥ 0

for all x, y > 0, we can write


a3 + b3 ab(a + b) a+b
≥ = ,
2 2 2c
and similarly
b3 + c3 b + c c3 + a3 c+a
≥ , ≥ .
2 2a 2 2b
Summing up these last 3 inequalities and applying the AM-GM Inequality, we get
8 a+b b+c c+a 8
a3 + b3 + c3 + ≥ + + +
(a + b)(b + c)(c + a) 2c 2a 2b (a + b)(b + c)(c + a)
s
a+b b+c c+a 8
≥4 4 · · ·
2c 2a 2b (a + b)(b + c)(c + a)
=4.

  

In the same year, Titu Zvonaru proposed in Revista de Matematica din Timisoara 2 (2018) a stronger
form of this inequality.
OBJ.139 Let a, b, c be positive real numbers such that abc = 1. Prove that
64
a3 + b3 + c3 + ≥ 11.
(a + b)(b + c)(c + a)

Solution: The expression a3 + b3 + c3 suggests appealing to Schur’s Inequality i.e.

a3 + b3 + c3 + 3abc ≥ ab(a + b) + bc(b + c) + ca(c + a),

or
a3 + b3 + c3 + 5abc ≥ (a + b)(b + c)(c + a).

Mathematical Reflections 6 (2023) 1


Using this inequality and AM-GM Inequality, we have
64 64
a3 + b3 + c3 + =a3 + b3 + c3 + 5abc + −5
(a + b)(b + c)(c + a) (a + b)(b + c)(c + a)
64
≥(a + b)(b + c)(c + a) + −5
(a + b)(b + c)(c + a)
s
64
≥2 (a + b)(b + c)(c + a) · −5
(a + b)(b + c)(c + a)
=11.

In both inequalities, the equality holds when a = b = c = 1.

  

The problem we set ourselves is what is the best constant k so that:


8k
a3 + b3 + c3 + ≥ 3 + k, (1)
(a + b)(b + c)(c + a)

for all a, b, c > 0 such that abc = 1.


1
In (1) we take a = b = t > 0, c = so we have
t2
1 4kt3
2t3 + + ≥ 3 + k,
t6 (t3 + 1)2
or  
1 4
(t − 1)2 + 2t3 + 3 + 5 − k ≥ 0.
t6 t
This is true for all t > 0 if and only if
 
1 3 4
k ≤ inf + 2t + 3 + 5 .
t>0 t6 t

Consider the function f : (0, ∞) 7→ R defined as


1 4
f (x) = 2
+ 2x + + 5.
x x
Since
2(x3 − 2x − 1) 2(x + 1)(x2 − x − 1)
f 0 (x) = = ,
x3 x3
√ ! √ !
1+ 5 1+ 5
we conclude that f is a decreasing function on 0, and a increasing function on ,∞ .
2 2
Therefore √ ! √
1+ 5 11 + 5 5
f (x) ≥ f =
2 2

11 + 5 5
for all x > 0 which means k ≤ .
2 √
11 + 5 5
Next, we will show that the inequality holds for k = ≈ 11.0901699 which would mean that this
2
value of k is the best. We have the following statement:

Mathematical Reflections 6 (2023) 2


Let a, b, c be positive real numbers such that abc = 1. Prove that
√ √
3 3 3 4(11 + 5 5) 17 + 5 5
a +b +c + ≥ .
(a + b)(b + c)(c + a) 2
When does equality hold?

Solution. To prove the inequality, we will use the SOS-Schur technique and the method of undetermined
coefficients (see [2]). Without loss of generality suppose that a ≥ b ≥ c. In homogeneous form, the inequality
can be written as follows

a3 + b3 + c3 − 3abc (11 + 5 5) [(a + b)(b + c)(c + a) − 8abc]
≥ ,
abc 2(a + b)(b + c)(c + a)

(a + b + c)(X + Y ) (11 + 5 5) [2cX + (a + b)Y ]
≥ ,
abc 2(a + b)(b + c)(c + a)
where we denote X = (a − b)2 ≥ 0, Y = (a − c)(b − c) ≥ 0. To prove this inequality, because a + b ≥ 2c, it
is enough to show that √
2(a + b + c)(a + c)(b + c) ≥ (11 + 5 5)abc.
We try using the Weighted AM-GM Inequality. Let α, β > 0 such that:
α
a  
b  a  α  b  2α+1 1
2α+1
a+b+c=α· +α· + c ≥ (2α + 1) c 2α+1 ,
α α α α
    β
a a β+1 β+1
1
a+c=β· + c ≥ (β + 1) c ,
β β
    β
b b β+1 β+1
1
b+c=β· + c ≥ (β + 1) c .
β β
We set the condition
α β
2α+1 + β+1 =1
1 2
2α+1 + β+1 = 1.

1+ 5
that passes on αβ = α + 1. Let’s choose α = β so α2 − α − 1 = 0 equation that has a positive root α = 2 .
Therefore
2(2α + 1)(α + 1)2
2(a + b + c)(a + c)(b + c) ≥ 2α 2α abc
α 2α+1 + α+1
2(2α + 1)(α + 1)2
= abc
α2
2(2α + 1)(α + 1)2
= abc
α+1

=2(5α + 3)abc = (11 + 5 5)abc
 √ 
that is exactly what we desired. The equality holds when a = b = c and a = b = 1+2 5 c.

  

An extension to 4 variables of this inequality would look like this:

16k
a4 + b4 + c4 + d4 + ≥ 4 + k, (2)
(a + b)(b + c)(c + d)(d + a)
for all a, b, c, d > 0 such that abcd = 1.

Mathematical Reflections 6 (2023) 3


Remarks. 1) For k = 4 the inequality results easily. By the Power Mean Inequalities, we have
 14
a4 + b4 + c4 + d4

a+b+c+d
≥ .
4 4

Also, by the AM-GM Inequality


4
(a + b + c + d)4

a+b+b+c+c+d+d+a
(a + b)(b + c)(c + d)(d + a) ≤ = .
4 16

Finally, using this and by the AM-GM Inequality

16 (a + b + c + d)4 45
a4 + b4 + c4 + d4 + ≥ +
(a + b)(b + c)(c + d)(d + a) 43 (a + b + c + d)4

≥2 42 = 8.

The equality holds when a = b = c = d.


2) The inequality also occurs for k = 7. First we prove the following inequality:
(Tran Le Bach-Vasile Cı̂rtoaje) If a, b, c, d > 0 then we have
X
a4 + b4 + c4 + d4 + 8abcd ≥ abc(a + b + c).
cyc

Solution. Without loss of generality suppose that d = min{a, b, c, d}and let a = d + x, b = d + y, c = d + z,


where x, y, z ≥ 0. After a few calculations, not very easy, we get the following inequality
! !
X X X X X
3 x2 − 2 xy d2 + 2 2 x3 − xy(x + y) d + x4 − xyz(x + y + z) ≥ 0,
cyc cyc cyc cyc cyc

clearly true because X X


x2 ≥ xy,
cyc cyc
X X X
2 x3 − xy(x + y) = (x + y)(x − y)2 ≥ 0,
cyc cyc cyc
X 1X 2 1X 2
x4 − xyz(x + y + z) = (x − y 2 )2 + z (x − y)2 ≥ 0.
cyc
2 cyc 2 cyc

Homogenizing the inequality (2) for k = 7, we get

a4 + b4 + c4 + d4 112abcd
+ ≥ 11. (3)
abcd (a + b)(b + c)(c + d)(d + a)

Now, we can normalize the inequalities with a + b + c + d = 4. Using


 4
a+b+b+c+c+d+d+a
(a + b)(b + c)(c + d)(d + a) ≤ = 16
4

and
a4 + b4 + c4 + d4 (a + b + c + d)(abc + bcd + cda + dab) X1
≥ − 12 = 4 − 12
abcd abcd cyc
a

Mathematical Reflections 6 (2023) 4


to prove (3) it suffices to show that
 
1 1 1 1
4 + + + + 7abcd ≥ 23.
a b c d

We prove this inequality using stronger Mixing Variable Method(see [3]). Note that the inequality is sym-
metric, so without loss of generality, we may assume a ≥ b ≥ c ≥ d. Denote by
 
1 1 1 1
f (a, b, c, d) = 4 + + + + 7abcd − 23.
a b c d

We have
 
b+d b+d
f (a, b, c, d)−f a, , c,
2 2
(b + d)2
   
1 1 4
=4 + − + 7ac bd −
b d b+d 4
2
(b − d) [16 − 7abcd(b + d)]
= ≥ 0,
4bd(b + d)

a+b+c+d 4
 
a+b+c+d
because abcd ≤ = 1 and b + d ≤ = 2. Hence, according to stronger Mixing
4 2
Variable Method, we only need to consider the inequality in case a = 4 − 3x, b = c = d = x ≤ 1. In this
case, the problem becomes  
1 3
4 + + 7x3 (4 − 3x) ≥ 23,
4 − 3x x
or
(x − 1)2 (63x4 − 42x3 − 35x2 − 28x + 48)
≥0
x(4 − 3x)
which is true for 0 < x ≤ 1.
3) We leave it to the readers to find better k constants, possibly the best k.

References

[1] Titu Andreescu, Marius Stănean, 116 Algebraic Inequalities from the AwesomeMath Year-Round
Program, 2018.

[2] Titu Andreescu, Marius Stănean, 118 Inequalities for Mathematics Competitions, 2019.

[3] Titu Andreescu, Marius Stănean, New, Newer, and Newest Inequalities, 2021.

Mathematical Reflections 6 (2023) 5

You might also like